Consumptive Coagulopathy Involving Amniotic Fluid Embolism: The Importance of Earlier Assessments for Interventions in Critical Care - Oda, Tomoaki (Crit Care Med, 2020)
OBJECTIVES: Amniotic fluid embolism is a rare disease that induces fatal coagulopathy; however, due to its rarity, it has not yet been examined in detail. The strict diagnostic criteria by Clark for amniotic fluid embolism include severe coagulopathy complicated by cardiopulmonary insufficiency, whereas the Japanese criteria also include postpartum hemorrhage or Disseminated Intravascular Coagulation in clinical practice. Amniotic fluid embolism cases with preceding consumptive coagulopathy may exist and are potential clinical targets for earlier assessments and interventions among amniotic fluid embolism cases fulfilling the Japanese, but not Clark criteria. The present study was performed to compare coagulopathy in the earlier stage between the amniotic fluid embolism patients diagnosed by Clark criteria (Clark group, n = 6), those by the Japanese criteria (Non-Clark group, n = 10), and peripartum controls and identify optimal clinical markers for earlier assessments of amniotic fluid embolism-related consumptive coagulopathy. DESIGN: Retrospective case-control study. SETTING: A single university-based center. Our amniotic fluid embolism registry program has accumulated clinical information and blood samples since 2003. PATIENTS: Amniotic fluid embolism patients in the Clark and Non-Clark groups between 2009 and 2017 and peripartum controls. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Clinical information was collected on hemoglobin levels, platelet counts, and coagulation- and fibrinolysis-related variables. Fibrinolytic parameters were also measured and compared among the three groups before blood transfusion. Fibrinogen levels in all patients in the Clark group and most in the Non-Clark group decreased earlier than hemoglobin levels, which was consistent with the high hemoglobin/fibrinogen ratio and, thus, is a promising clinical marker for the earlier assessment of amniotic fluid embolism-related consumptive coagulopathy. CONCLUSIONS: Earlier evaluations of consumptive coagulopathy and hyperfibrinolysis using the hemoglobin/fibrinogen ratio following preemptive treatment may reduce the occurrence or prevent the aggravation of severe coagulopathy in amniotic fluid embolism patients.